2005
DOI: 10.1007/s00253-005-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of single-cell protein from deproteinized whey concentrates

Abstract: Deproteinized sweet and sour cheese whey concentrates were investigated for their suitability as substrates for the production of single-cell protein with Kluyveromyces marxianus CBS 6556 up to a 100-l scale. An important factor for gaining high cell concentrations was the use of the Crabtree-negative strain K. marxianus CBS 6556. Supplements such as trace elements, ammonium and calcium were required for the complete conversion of sweet whey concentrates into biomass, whereas sour whey concentrates had to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 15 publications
1
65
0
1
Order By: Relevance
“…These media presented lower initial substrate concentrations (Table 1) , respectively, with significant differences between them (p > 0.05). Similar work carried out by Schultz et al (2006) showed an efficiency of 83.00% in COD reduction after whey fermentation. According to the results, even after the microorganism reached maximum growth ( Figure 2B), the COD continued decreasing until reaching a plateau after 48 hours of fermentation.…”
Section: Chemical Oxygen Demand (Cod)supporting
confidence: 70%
See 1 more Smart Citation
“…These media presented lower initial substrate concentrations (Table 1) , respectively, with significant differences between them (p > 0.05). Similar work carried out by Schultz et al (2006) showed an efficiency of 83.00% in COD reduction after whey fermentation. According to the results, even after the microorganism reached maximum growth ( Figure 2B), the COD continued decreasing until reaching a plateau after 48 hours of fermentation.…”
Section: Chemical Oxygen Demand (Cod)supporting
confidence: 70%
“…In this context, dairy products represent an important sector of the food industry, from both the economic and social points of view. The main byproduct is whey, or cheese whey, which can cause serious environmental problems due to its high organic load from biodegradable matter, having a Chemical Oxygen Demand (COD) of about 50,000 to 80,000 mg L -1 (Schultz, Chang, Hauck, & Syldatk, 2006, Vincenzi et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Several agro-industrial wastes have been utilized as economic substrates to produce SCP, including potato residues and oil mill wastewater [100][101][102]. Other wastes like fruit pomaces, whey, molasses and lignocellulosic biomass have also been widely studied [103][104][105][106].…”
Section: Production Of Food Microorganisms Using Potato Pulp and Procmentioning
confidence: 99%
“…In literature, the production of bioethanol (Ghaly & El-Taweel, 1997;Zafar & Owais, 2006), vinegar (Parrondo et al, 2003), antibiotics, e.g. the bacteriocin Nisin, (Hickmann Flôres & Monte Alegre, 2001), yeasts for yeast extract production ( de Palma Revillion et al, 2003), surface active compounds like sophorolipids (Daniel et al, 1999), single-cell protein (Schultz et al, 2006), "green bioplastics" like Polyhydroxyalkanoates, PHAs, (Ahn et al, 2000;Ahn et al, 2001;Kim, 2000;Povolo & Casella, 2003;Koller et al, 2007 a,b), and lactic acid that is of importance as food additive (E 270), for pharmaceutical matrices, and as monomer for the production of polylactic acid (PLA) is described (Kim et al, 1995). In addition, the induction of high-celldensity production of recombinant proteins can be accomplished by providing whey (Viitanen et al, 2003).…”
Section: General: the Need For Sustainable Utilization Of Wheymentioning
confidence: 99%